The fisheries of Timor-Leste: A 4-year time series analysis covering the COVID-19 pandemic - Veillat, Sarah; Tilley, Alexander; Reis Lopes, Joctan dos; Cagua, Fernando; Longobardi, Lorenzo; Kolding, Jeppe (WorldFish, 2022)
The time series of data used encompasses the COVID-19 pandemic, and our findings suggest that SSF in Timor-Leste were fairly resilient to the impact. Although they experienced a decline in the market value of the catch, it does not appear to have been as influential as in other countries, where decreases in fishing effort were seen. It is possible that the limited export of aquatic foods from Timor-Leste, and its modest tourism sector, sheltered the fisheries from shocks seen in the fishing sector of other nations. This reflects the persistence of SSF to generate food and income where formal markets and global supply chains are extremely limited. With increasing attention and investment in the country’s fisheries sector to achieve national development goals, it will be critical to consider if modernization and a focus on increasing production will benefit those with the most pressing food and nutritional needs, as well as environmental sustainability. This report provides a benchmark against which to track the progress and development of the fisheries sector in Timor-Leste, and serves as a case study for low-cost digital monitoring of fisheries in data-deficient scenarios.